International Students Adaptation Process in Malaysian Public Universities: A Social Communication Challenge - Yus Sharmiza Yushriman; Isma Rosila Ismail; Che Hasniza Che Noh; Roswati Abdul Rashid (Penerbit Universiti Kebangsaan Malaysia, 2024)
Education Malaysia Global Services (EMGS) is a national education provider in Malaysia that is specifically designed to manage international students. It offers various services, such as assistance with living costs, transportation rates, and necessary documentation for international students pursuing studies in Malaysia. This initiative aligns with the Ministry of Higher Education's objective of becoming an international education hub while providing exemplary hosting services. Malaysia's diverse environment creates a perception of harmony and ease of adaptation among international students. This research explores the adaptation process of postgraduate international students enrolled in Malaysian public universities, focusing on twelve students from four universities: UPM, UKM, UM, and USM. Qualitative data will be gathered through semi-structured interviews, and analysis will be conducted using the colour-coding technique with ATLAS.ti software. The findings indicate that some international students still face language challenges and context misunderstandings during interactions with locals, particularly those visiting Malaysia for the first time. In contrast, international students from other countries do not encounter significant language barriers. Addressing the communication barriers faced by international students during their stay in Malaysia is crucial, and the Ministry of Higher Education can utilise the results of this study to shape guidelines and policies that cater to the needs of international students as a host country.